Anatomic Parameters for Instrumentation of the Sacrum and Pelvis: A Systematic Review of the Literature. (August 2018) - Katsuura, Yoshihiro; Chang, Eric; Sabri, Shahbaaz A.; Gardner, Warren E.; Doty, Jesse F.
Abstract : Introduction: Multiple cadaver and radiographic analyses have been performed to define the surgical anatomy of the sacrum and pelvis. We provide a comprehensive review of this information, creating an accurate anatomic guide for practice and research. Methods: A systematic review was performed to identify publications citing sacral or iliac morphometric parameters based on cadaver or radiographic anatomy. Results: A total of 780 abstracts were evaluated. Fifty-six articles were included for final review and grouped into four sections: (1) bone density, (2) bony corridors, (3) screw length and trajectory, and (4) neurovascular and alimentary anatomy. Conclusion: A systematic analysis of the radiographic and gross anatomic features of the sacrum has yet to be published. This review includes details on the spatial arrangement of the S1 and S2 pedicle screws, sacroiliac screws, iliac screws, S2 alar iliac screws, and pelvic neurovascular anatomy. The study can be referenced by clinicians for sacral dissection, implant application, and ongoing advances in orthopaedic research. Study Design: Systematic review Level of Evidence: Level IV